The Effect of Single and Double Dose Platelet Apheresis on Platelet Count A Thrombopoietin Levels and Percentage of Immature Platelet Fraction of Donor Post Donation - Aulia Ramadhan Supit; Anzhari, Della Hashfi; Saptuti Chunaeni; Rahajuningsih Dharma Setiabudy (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Thrombapheresis is commonly used to obtain platelet concentrates; however, different collection doses may affect donor hematological responses. This study aimed to compare the effects of single-dose and double-dose thrombapheresis on platelet count, thrombopoietin (TPO) levels, and immature platelet fraction (IPF). A prospective comparative study with repeated measures was conducted in eight healthy donors (n = 8; 4 per group) at the Indonesian Red Cross Blood Donation Unit, Tangerang. Blood samples were collected before, immediately after, and on day 2 and day 4 post-donation. Platelet count and IPF were measured using an automated hematology analyzer, while TPO levels were assessed by ELISA. Data were analyzed using two-way ANOVA and Pearson correlation (p < 0.05). Platelet counts decreased immediately after thrombapheresis (23% in single-dose; 24% in double-dose) and gradually recovered. Significant effects of time and dose were observed (p < 0.05), but no difference between groups at day 4 (p > 0.05). TPO increased in both groups (50% vs 27%), and IPF changes were not significant (p > 0.05). A positive but non-significant correlation between TPO and IPF was found. Both procedures cause transient platelet reduction with gradual recovery. Findings should be interpreted cautiously due to the small sample size.